Sustainable Supply Chain Management Practice of Ethiopian Textile and Apparel Manufacturing Industry - Eyob Minbale; Berihun Bizuneh; Wendosen Seife Haile; Shalemu Sharew; Tinsaye Asfaw; Saba Mekonnen; Ruth Tadesse; Lioul Getachew; Kumlachew Bitew (Journal of Engineering)
Next to the oil industry, the apparel industries are strongly criticized for their negative impact on the ecosystem. Due to the current global trend, manufacturing industries are expected to consider sustainability issues beyond conventional business goals. In this regard, the study investigates the Ethiopian apparel and textile manufacturing industries’ sustainable supply chain management (SSCM) practices. A descriptive research design methodology using a cross-sectional survey was used. Data were collected through self-administered questionnaires. A simple random sampling technique to decide sample size and a purposive sampling technique to select respondents were employed. A total of 71 participants provided a valid response. The metrics for the survey were developed from different literature, and structural equation modeling was used for data analysis. The results demonstrated that the state of the implementation of SSCM practices by the fashion manufacturing industry in Ethiopia is still in its promising stages. The hypotheses test results showed that SSCM practices positively impact SSCM performance and competitiveness at p values of 0.05, except environmental practices with economic performance. The study provides additional insight into the growing field of literature that examines the relationships among SSCM practices, performance, and competitiveness. The findings offer insight for industrial policymakers to improve sustainability for global competitiveness. The Ethiopian government is making significant efforts to boost the manufacturing sector through the “Let Ethiopia Produce” campaign, and sustainability is among the significant necessities for the global competitiveness of the Ethiopian manufacturing industry.